Exploitation of spent mushroom substrate as mulch for the management of rhizome rot complex disease of ginger - Remya J S (Department of Plant Pathology, College of Horticulture, 2012)
Spent mushroom substrate (SMS) is the composted organic material remained after the harvest of a crop of mushroom and it is rich in plant nutrients including minerals and was used as manure in different crops including ginger. Recent findings illustrate that substrate after one cycle cultivation of mushroom can be used for disease management. So far no attempt has been made on the use of spent mushroom substrate from oyster mushroom, against rhizome rot complex disease of ginger. Under these circumstances, a study was conducted to know the effectiveness of oyster mushroom SMS to control the rhizome rot complex disease of ginger. Bacterial wilt and soft rot are the two common rhizome rot diseases of ginger. Ginger plants showing typical wilt symptoms and soft rot symptoms were collected from the farmer’s field. The fungal pathogen Pythium aphanidermatum and the bacterial pathogen, Ralstonia solanacearum were isolated from the rhizomes showing typical symptoms, and pure cultures were maintained. Since Pleurotus florida and P. sajor-caju are the most suitable mushroom species in Kerala, they were selected for the production of spent mushroom substrate. The substrate used were agricultural waste materials like paddy straw, saw dust and neopeat. The enumeration of microorganisms at different stages of mushroom growth were made and the fungi commonly observed were Aspergillus sp. (FA-2 and FA-3) and Trichoderma sp. (FA-1). Maximum number of microbial population was noticed in paddy straw, whereas it was minimum in neopeat. From four different stages of mushroom growth, five different types of bacteria, BA-1, BA-2, BA-3, BA-4 and BA-5 were observed. An in vitro evaluation study was conducted to find out the efficiency of isolated organisms against the pathogens P. aphanidermatum and R. solanacearum. Among the bacterial isolates tested against P. aphanidermatum, BA-4 and BA-5 were effective, whereas against R. solanacearum, only BA-5 was found effective. All the three fungal isolates, FA-1, FA-2 and FA-3 gave 100 per cent inhibition against both the pathogens. But FA-1 was the most effective one. These five antagonists were selected for the compatibility studies by dual culture technique. The selected fungal antagonist FA-1 was identified as Trichoderma viride by studying cultural and morphological characters. The bacterial isolates BA-4 and BA-5 were identified as Pseudomonas aeruginosa and Klebsiella pneumoniae respectively. The effect of spent mushroom substrate for the management of rhizome rot complex disease of ginger was assessed under pot culture conditions. Two separate experiments were conducted for the management of P. aphanidermatum and R. solanacearum. All the treatments were applied at three times- at the time of planting, 60 DAP and 120 DAP. Among the various treatments for the management of both the pathogens associated with rhizome rot complex disease, T. viride from SMS and paddy straw SMS of P. sajor-caju as mulch were found to be the best giving cent per cent disease control. In control treatment, cent per cent disease incidence was noticed. In the experiment for the management of P. aphanidermatum, hundred per cent germination was noticed in the treatment, T. viride from SMS + Reference culture T. viride. Among the treatments with SMS as mulch, paddy straw SMS of P. sajor-caju showed better germination percentage. But in the experiment for the management of R. solanacearum, the treatment Klebsiella pneumoniae showed 100 per cent germination followed by the treatment T. viride from SMS. The growth parameters like number of tillers, number of leaves per tiller and height of tillers were highest in the treatment T. viride from SMS, at two, three, four and five months of planting, in the experiment for the management of P. aphanidermatum. But in the experiment for the management of R. solanacearum, the treatment paddy straw SMS of P. sajor-caju as mulch showed highest number of tillers. Number of leaves per tiller was highest in the treatment K. pneumoniae + reference culture P. fluorescens, in the first three months and the treatment with paddy straw SMS of P. sajor-caju as mulch for the next two months. Height of tillers was observed maximum in the treatments applied with T. viride from SMS. The same trend was noticed in the case of yield also. In the experiment for the management of P. aphanidermatum, highest yield was observed in the treatment T. viride from SMS. But in the experiment for the management of R. solanacearum, the treatment paddy straw SMS of P. sajor-caju as mulch produced highest yield. SMS is rich in microflora with antagonistic effect against pathogenic microorganisms associated with ginger plants. From the pot culture experiment it was clear that for the management of R. solanacearum and plant growth promotion, best treatment is paddy straw SMS of P. sajor-caju as mulch. High cellulolytic capacity of P. sajor-caju favour the maximum degradation of the substrate, thereby provides a niche for the multiplication of favourable microorganisms with antagonistic effect. Whereas, best treatment for the management of P. aphanidermatum and plant growth enhancement is T. viride from SMS. It was found to be better than reference culture T. viride. In addition the beneficial microorganisms may be having plant growth promoting activity which contributes to increased yield in the various treatments. So from the present study, it can be concluded that the use of paddy straw SMS of P. sajor-caju as mulch, along with the application of T. viride from SMS can be considered as an effective management practice against the rhizome rot complex disease of ginger. Depending on the location and climatic condition in which the mushroom crop is raised, the microorganisms harbouring in SMS will vary and they can be used for disease management in various crops.